DEVELOPMENT OF THE CONCEPT OF THE METHOD OF USING BLOCKCHAIN TECHNOLOGY FOR BUILDING A MESSAGE EXCHANGE SYSTEM - Poberezhnyk, Vasyl; Opirskyy, Ivan (Ukrainian Information Security Research Journal, 2023)
In modern realities, fast information exchange is an important aspect of human life. That is why information, that circulates in message exchange systems, requires to be secured. There are several possible ways to implement this, but the fast development of technologies forces us to search for alternate ways. One of the possible ways may become blockchain technology, which is not widely used in such a context, but found its popularity in the sphere of cryptocurrency and decentralized finances for its user privacy-preserving possibilities. The main idea of blockchain consists of that this is the decentralized distributed network that allows storing of information in an immutable way and provides access to it for all users of the network alongside prohibitions of the existence of users with exceptional privileges, which allows considering the blockchain technology as the base of a quality system for message exchange system which will provide integrity and availability of information. This article examines the features of blockchain technology and decentralized applications, analyzes the weaknesses and strengths and opportunities they can offer to such a system, and proposes a concept of the method of using blockchain technology to build a messaging system. In addition, the shortcomings of such a system are analyzed and methods to overcome them are proposed.